Resistance to Wheat streak mosaic virus and Triticum mosaic virus in wheat mediated by RNAi - Cruz, Luisa Fernanda (Kansas State University, 2009)
Wheat streak mosaic virus (WSMV) and Triticum mosaic virus (TriMV), are two of the major viruses in the Great Plains of the United States. Cultural practices and mite vector control are the primary methods of disease management; however, they are not fully effective. Resistant varieties are also deployed, although some of the lines present temperature sensitive resistance or negative agronomic properties are linked to resistance. Alternative approaches to viral resistance are needed. RNAi has been shown to play a role in viral defense response and has been successfully used as a biotechnological tool to preprogram viral resistance in transgenic plants. RNAi reduces the expression of specific genes by targeting the accumulation of mRNA. The mechanism is activated by the presence of dsRNA, which is processed into small non-coding sequence that serves as a guide for degrading RNA in a sequence specific manner. In this work, the RNAi approach was used to elicit resistance against WSMV and TriMV. Immature embryos of the wheat cv "Bobwhite" were independently co-transformed with pAHC20, containing the bar gene for glufosinate selection, and either the hairpin construct targeting the coat protein of WSMV or TriMV. After tissue culture, PCR was used to determined the presence of the RNAi CP transgene in putative transformed plants. Eight WSMV and ten TriMV CP RNAi transgenic plants were obtained from the bombardment experiments. Transgenic T1 and T2 seeds were collected and transgene expression was established through RT-PCR. In order to determine viral resistance, T1 and T2 progeny was mechanically inoculated. ELISA results indicated a differential resistance response among the tillers evaluated in each line in T1 generation for both WSMV and TriMV constructs. In T1 generation resistance was seen in up to 60% of the plants evaluated for both constructs, although some events that showed transgene presence did not exhibited resistant phenotype. Analyses of transgene presence and expression in T2 generation evidenced events of transgene silencing and deletion. Regardless of these phenomena, consistent resistance response in two lines of WSMV CP construct and one TriMV CP transgenic line was found.
Keywords: Wheat; Resistance; Virus; Interference RNA; Agriculture, Plant Pathology (0480)